MATHEMATICS MODEL OF MEDIA COVERAGE ON THE DECREASING OF ALCOHOL CONSUMPTION - KIPTANE ARGA (NIM : 10113057), HERADA
In 2010, the World Health Organization (WHO) approved a resolution that supports a global strategy to reduce the harmful of alcohol consumption. In this case, WHO urges countries to strengthen the national response to public health problems caused by harmful alcohol users. One way to solve this case is create, compile, and disseminate scientific information on alcohol consumption as well as social and health consequences associated. This Final Project explores a model of social epidemic that describes alcoholism with media coverage as one way to reduce the harmful use of alcohol. Population models used are Susceptible, Infected, and Recovered (SIR) model which is divided into three compartments with added influence of the media as a form of further development of this model. The main indicator used in this modeling is Basic Reproductive Number 〖(R〗_0) that built analytically by using The Next Generation Matrix. R_0 will determine a non-endemic and endemic condition of the model used. Some of fundamental properties of the model including existence and positivity are investigated in this Final Project. The stability of all equilibrium is also included in this Final Project. Numerical simulations ranging from non-endemic to endemic states are presented in this Final Project. Sensitivity analysis is performed to illustrate the results of media influence on alcoholics. The results show that media coverage is an effective step to make alcoholics stop consuming alcohol.